Analysis of bending-induced degradation of orbital angular momentum modes in optical fibers - Lee, In Joon; Song, Joohyung; Kim, Sangin (Photonics, 2019)
In this work, bending-induced deterioration of orbital angular momentum (OAM) modes in ring core fiber (RCF), photonic crystal fiber (PCF), and vortex fiber (VF) was theoretically investigated: Bending losses, coupling losses, and intermodal crosstalk at the interface between straight and bent optical fibers were investigated from the modal analysis of those three types of OAM mode fibers. In addition, the degradation of a topological charge number of an OAM mode due to the bending-induced birefringence and horizontal mode asymmetry was also investigated. Our investigation revealed that, in all aspects, the PCF is most robust to bending among the three types of optical fibers, and the most serious bending-induced problem in the VF and the RCF is the degradation of the topological charge number. The allowed minimum bending radii of VF and RCF appeared to be ~15 and ~45 mm, respectively, for the specific structures considered in this work. We expect that the methodology and results of our quantitative analysis on bending-induced degradation of OAM modes will be of great use in the design of OAM mode fibers for practical use.
Keywords: Fiber bending effect; Orbital angular momentum (OAM), vortex fiber; Photonic crystal fiber; Ring core fiber; Topological charge number